Religious Tolerance and Family Dynamics: A Study of Interfaith Households in Solok Selatan, West Sumatra - Rahmadania, Selvi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This study explores the dynamics of tolerance within interfaith families, focusing on how these families navigate religious differences and their impact on household harmony and the religious upbringing of their children. Conducted in Jorong Taratak Baru, Solok Selatan, West Sumatra, this research employs a qualitative methodology, utilizing fieldwork through observations, in-depth interviews, and document analysis. Primary data were collected directly from interfaith families in the area, while secondary sources, including scholarly articles, theses, and books on tolerance, provided contextual insights. The research aims to understand how tolerance is cultivated and sustained within interfaith households. Findings reveal that despite societal perceptions of interfaith marriages as fraught with challenges, these families demonstrate remarkable resilience and adaptability. They establish harmonious domestic environments, comparable to those of single-faith households, by fostering mutual respect and embracing diversity. The study highlights that the success of interfaith households hinges on the families’ conscious efforts to nurture tolerance, ensuring that differences are not perceived as barriers but as opportunities for mutual enrichment. This research contributes to the broader discourse on interfaith relations, emphasizing the potential of tolerance to bridge divides in increasingly pluralistic societies. By showcasing how interfaith families thrive despite challenges, this study underscores the importance of fostering understanding and acceptance in multicultural contexts.